THE CITY POLICE OF SMOLENSK PROVINCEDURING THE NIKOLAYEV ERA: ISSUES OF PERSONNEL POLICY - Chikov S.S. (Вестник Брянского государственного университета)
The article analyses the personnel policy in the city police in Smolensk province in the second third of the XIX century. When considering the degree of study of the problem, special attention is paid to modern historiography. The source base of the research are the regulatory legal acts of the Russian Empire in the end of the XVIII century - the first half of the XIX century, the main block consisted of the records of the Russian State Archive of the Police Department as well as of the State Archive of the Smolensk region in the fonds of the Smolensk Governor's Office and the Gzhatsk city police. The analysis of legislative base and archival sources for the first time enabled the author to give an almost complete list of Smolensk policemen beginning from the foundation of the Office of Piety in Smolensk in 1804 to its abolition in 1862. The author reflects specific features of the personnel policy during Nikolaev's epoch by the example of Smolensk province and reveals the peculiarities of everyday life in the provincial towns in the second third of the 19th century. The author's conclusion is the thesis that Smolensk province reflects both strong and weak sides of the personnel policy of the Russian absolutism in the second third of the XIX century and, in this connection, serves as a representative example of the phenomenon.